The Synthetic Effects of Iron with Sulfur and Fluorine on Photoabsorption and Photocatalytic Performance in Codoped - Xiaohua Li; Jibao Lu; Ying Dai; Meng Guo; Baibiao Huang (International Journal of Photoenergy)
The structural and electronic properties of iron-fluorine (Fe-F) and iron-sulfur (Fe-S) codoped anatase TiO2 are investigated by first-principles based on density functional theory. Our results show that the formation energy of codoped system is lower than that of single-element doping, which indicates the synergic effect of codoping on the stability of the structure. Codopants introduced impurity gap states resulting in the electron transition energy reduction and thus the visible light absorption observed in the samples. It is concluded that Fe-S should be a better codoping pair because Fe-S codoping introduces extended impurity states resulting in stronger visible light absorption than that of Fe-F codoped compounds. This work gives understanding to the recent experiment and provides the evidence of choosing the more effective co-dopants in TiO2.